The Evolution of Philosophical Thoughts and Their Influence on Planning Concepts, Education and Profession - Sudaryono Sastrosasmita (The Institute for Research and Community Services, Institut Teknologi Bandung, 1998)
Shifts of planning thoughts in the academia from the rational tradition towards new directions that was witnessed in (lie decade of 1980s, seemed to have more serious attention in this era of globalization, In order to delineate the future directions of planning theories, education, and profession, this article tries to review some of the major philosophical thoughts and their influence on the development of planning thoughts, education, and profession. Theocentrism, utopianism, positivism, rationalism, and phenomenology are five major philosophical thoughts which have shown through history fundamental influence in setting the directions of planning thoughts, education, and profession. They are discussed in this article.